2016
DOI: 10.14348/molcells.2016.2226
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Streptomyces avermitilis CYP107W1-Oligomycin A Complex and Role of the Tryptophan 178 Residue

Abstract: CYP107W1 from Streptomyces avermitilis is a cytochrome P450 enzyme involved in the biosynthesis of macrolide oligomycin A. A previous study reported that CYP107W1 regioselectively hydroxylated C12 of oligomycin C to produce oligomycin A, and the crystal structure of ligand free CYP107W1 was determined. Here, we analyzed the structural properties of the CYP107W1-oligomycin A complex and characterized the functional role of the Trp178 residue in CYP107W1. The crystal structure of the CYP107W1 complex with oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Recently Han et al [77] reported a 2.1 Å structure (PDB 4WPZ) for P450 107W1, an enzyme involved in C12 hydroxylation in the biosynthesis of the macrolide oligomycin A. The substrate was not present in the crystal, but early in 2016 a new structure with the product oliomycin A has been published [78], The structure (PDB 4WQ0) indicates that Trp-178, located in the open pocket of the active site, may be a critical residue for the productive binding conformation.…”
Section: Recent Bacterial P450 Structuresmentioning
confidence: 99%
“…Recently Han et al [77] reported a 2.1 Å structure (PDB 4WPZ) for P450 107W1, an enzyme involved in C12 hydroxylation in the biosynthesis of the macrolide oligomycin A. The substrate was not present in the crystal, but early in 2016 a new structure with the product oliomycin A has been published [78], The structure (PDB 4WQ0) indicates that Trp-178, located in the open pocket of the active site, may be a critical residue for the productive binding conformation.…”
Section: Recent Bacterial P450 Structuresmentioning
confidence: 99%
“…In the present study, olmAI expression in S. avermitilis was directly negatively regulated by the metalloregulatory protein IdeR, indicating a direct effect of IdeR on secondary metabolism. Han et al found that cytochrome P450 enzyme CYP107W1 in S. avermitilis hydroxylated the C-12 of oligomycin C to produce oligomycin A, via the catalytic center of the heme group (50). Thus, the elevated iron concentration in DideR may stimulate oligomycin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…CYP171A1, a P450 enzyme encoded by the aveE gene from S. avermitilis , is involved in the biosynthesis of the avermectins, where it catalyzes the formation of the furan ring (Han et al ., 2016; Lamb et al ., 2003). Our previous effort to purify functional, recombinant CYP171A1 holoenzyme using an E. coli expression system was not successful.…”
Section: Discussionmentioning
confidence: 99%
“…S. avermitilis was first isolated in Japan in 1979, and was screened by Merck Sharp & Dohme, resulting in the discovery of the avermectins, which are famous anthelmintic and insecticidal agents ( Burg et al ., 1979 ; Demain, 1999 ). CYP171A1, a P450 enzyme encoded by the aveE gene from S. avermitilis , is involved in the biosynthesis of the avermectins, where it catalyzes the formation of the furan ring ( Han et al ., 2016 ; Lamb et al ., 2003 ). Our previous effort to purify functional, recombinant CYP171A1 holoenzyme using an E. coli expression system was not successful.…”
Section: Discussionmentioning
confidence: 99%